The intergenerational cycle of teenage motherhood: an ecological approach. - Meade, Christina S; Kershaw, Trace S; Ickovics, Jeannette R (Health psychology : official journal of the Division of Health Psychology, American Psychological Association, 2008)
Daughters of teenage mothers have increased risk for teenage childbearing, perpetuating intergenerational cycles. Using Ecological Systems Theory, this study prospectively examined risk factors for teenage childbearing among a national sample of adolescent girls.
Keywords: Adolescent; Adult; Age Factors; Family; Female; Humans; Intergenerational Relations; Maternal Age; Middle Aged; Mothers; Pregnancy; Pregnancy in Adolescence; Questionnaires; Risk Factors; Social Environment